NF-κB Links TLR2 and PAR1 to Soluble Immunomodulator Factor Secretion in Human Platelets - Damien, Pauline; Cognasse, Fabrice; Payrastre, Bernard; Spinelli, Sherry L.; Blumberg, Neil; Arthaud, Charles-Antoine; Eyraud, Marie-Ange; Phipps, Richard P.; McNicol, Archibald; Pozzetto, Bruno; Garraud, Olivier; Hamzeh-Cognasse, Hind (Frontiers in Immunology, 2017)
The primary TLR-mediated immune cell response pathway common for all TLRs is MyD88-dependent activation of NF-kB, a seminal transcription factor for many chemokines and cytokines. Remarkably, although anucleate platelets express the NF-κB machinery, whose role in platelets remains poorly understood. Here, we investigated the contribution of NF-κB in the release of cytokines and serotonin by human platelets, following selective stimulation of TLR2 and PAR1, two, classical or not, a classical and non-classical pattern-recognition receptor, respectively, able to participate to the innate immune system. We discovered that platelet PAR1 activation drives the process of NF-κB phosphorylation, in contrast to TLR2 activation, which induces a slower phosphorylation process. Conversely, platelet PAR1and TLR2 activation induces similar ERK1/2, p38 and AKT phosphorylation. Moreover, we found that engagement of platelet TLR2 with its ligand, Pam3CSK4, significantly increases the release of sCD62P, RANTES and sCD40L; this effect was attenuated by incubating platelets with a blocking anti-TLR2 antibody. This effect appeared selective since no modulation of serotonin secretion was observed following platelet TLR2 activation. Platelet release of sCD62P, RANTES and sCD40L following TLR2 or PAR1 triggering was abolished in the presence of the NF-κB inhibitor Bay11-7082, while serotonin release following PAR1 activation was significantly decreased. These new findings support the concept that NF-κB is an important player in platelet immunoregulations and functions.